Dampak Stres Kerja dan Beban Kerja pada Turnover Intention di Bank Nagari Sumatera Barat - Liza Laroza; Lidya Martha; Febsri Susanti; Riri Mayliza; Sumiati Sumiati (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study was to examine the effect of work stress and workload on employee turnover intention at PT. Bank Nagari West Sumatra. This study uses a quantitative method with a survey research type, the sample calculation in this a sample size of 95 employees at PT. Bank Nagari West Sumatra. The data collection method used a questionnaire, the analysis tool with multiple linear regression. The results of the study concluded that partially work stress has a positive and significant effect on employee turnover intention at Bank Nagari West Sumatra. While workload does not have a significant effect on employee turnover intention at Bank Nagari West Sumatra.